(untitled) (Texas Journal of Philology, Culture and History, 2024)
This text explores the role of phraseological comparisons in intensifying adjectives in the French language. These fixed expressions, often rooted in historical and cultural contexts, amplify the intensity of adjectives, sometimes adding emotional or humorous connotations. Examples include both traditional idiomatic expressions and more creative constructions found in contemporary literature, highlighting their expressive and emotive potential